Hypertension. Issue 6 (13th March 2015) - te Riet, Luuk; van Esch, Joep H.M.; Roks, Anton J.M.; van den Meiracker, Anton H.; Danser, A.H. Jan
<x xml:space="preserve">Abstract</x> Blockers of the renin–angiotensin–aldosterone system (RAAS), that is, renin inhibitors, angiotensin (Ang)-converting enzyme (ACE) inhibitors, Ang II type 1 receptor antagonists, and mineralocorticoid receptor antagonists, are a cornerstone in the treatment of hypertension. How exactly they exert their effect, in particular in patients with low circulating RAAS activity, also taking into consideration the so-called Ang II/aldosterone escape that often occurs after initial blockade, is still incompletely understood. Multiple studies have tried to find parameters that predict the response to RAAS blockade, allowing a personalized treatment approach. Consequently, the question should now be answered on what basis (eg, sex, ethnicity, age, salt intake, baseline renin, ACE or aldosterone, and genetic variance) a RAAS blocker can be chosen to treat an individual patient. Are all blockers equal? Does optimal blockade imply maximum RAAS blockade, for example, by combining ≥2 RAAS blockers or by simply increasing the dose of 1 blocker? Exciting recent investigations reveal a range of unanticipated extrarenal effects of aldosterone, as well as a detailed insight in the genetic causes of primary aldosteronism, and mineralocorticoid receptor blockers have now become an important treatment option for resistant hypertension. Finally, apart from the deleterious ACE-Ang II-Ang II type 1 receptor arm, animal studies support the existence of protective aminopeptidase A-Ang III-Ang II type 2 receptor and ACE2-Ang-(1 to 7)-Mas receptor arms, paving the way for multiple new treatment options. This review provides an update about all these aspects, critically discussing the many controversies and allowing the reader to obtain a full understanding of what we currently know about RAAS alterations in hypertension.